NEEDS ANALYSIS OF TEXT TO SPEECH BASED WORKSHEETS FOR TENTH GRADE STUDENTS AT THAWALIB GUNUNG PADANG PANJANG - Kuntum Haviza Husna; Rahmawati; Fauzana Annova (Journal International of Lingua and Technology, 2026)
This study aims to analyze the needs for developing a Text to Speech (TTS) based listening worksheet (LKPD) to improve Arabic listening skills for tenth-grade students at Thawalib Gunung Padang Panjang. The research employed a quantitative approach using a one-group pretest–posttest pre-experimental design. Data were collected through needs analysis questionnaires administered to both the Arabic teacher and students, focusing on teaching materials, teacher requirements, and student learning needs. The results show that 97.5% of teachers and 97% of students strongly support the development of a TTS-based LKPD. Students expressed the need for listening exercises with clear pronunciation models, repeated exposure, and interactive visual aids, while teachers required materials that facilitate independent practice, save instructional time, and align with the curriculum. The integration of TTS technology leverages existing infrastructure, such as TVs and personal devices, providing an innovative and practical solution to overcome the limitations of current resources. The study contributes to educational practice by offering a student-centered instructional tool that enhances listening skill acquisition, promotes independent learning, and supports effective Arabic language instruction. These findings highlight the potential of technology-assisted worksheets to enrich the learning environment and address gaps in conventional teaching materials.